Siamo parte della soluzione: la via contadina per la sovranità alimentare - Giunta, Isabella (My University, 2014)
The subject of the thesis is the international peasant movement Vía Campesina, born in 1993 with the aim to fight against the invisibility imposed to the peasantry by the dominant narrative of agricultural modernization. Vía Campesina claims that the peasant social figure is contemporaneous and that is caracterized by the ability to innovate and to produce alternative visions of future. Its main proposal is the food sovereignty. Our study is focused on the collective actions aimed to promote the food sovereignty principles and conducted at national level by organizations affiliated to this international movement. We analyze the articulation between heterogeneous actors, their mechanisms to produce collective horizons and actions, as well as the impacts produced, especially in terms of institutional innovation. In reference to the Ecuadorian case study, the Constitution (2008) declared food sovereignty a strategic goal and a government obligation, embracing many of the proposals put forth since the late 1990s by Ecuadorian federations linked to Vía Campesina. The issue of food sovereignty has expanded from the inner circles of peasant organizations to the wider context of the whole Ecuadorian society. We provide an overview of this process, describing the collective actions that made it possible. Moreover, we attempt to explain the reasons why the ‘Agrarian Revolution’ is currently evaluated as weak, and the motivations for a gap between constitutional mandates and the ongoing official policies. The Italian case study shows fewer results, mainly concentrated at local and European level, however the organizations linked to Via Campesina are engaged in political advocacy to obtain institutional instruments aimed to promote food sovereignty. In this framework, we consider that the food sovereignty proposal works as a polysemic and an open signifier, capable of providing a renewed sense to the historical peasant claims, such as access to land and other means of production, but joining them with new buzzwords, dictated by the political, socio-ecologic and economic global transformations, but also by the changes experienced by the same social actors. Finally, there is a constituent power in the collective action conducted by the organizations of Via Campesina and aimed to political advocacy: they work as motors of social and institutional transformations.
Dottorato di ricerca in Conoscenze e innovazioni per lo sviluppo, XXVI ciclo. A.a. 2013-2014
Keywords: Politica agraria; Sovranità alimentare